COMPARATIVE BEHAVIOUR PROBLEMS AMONG PRIMARY SCHOOL CHILDREN OF GRADE-5 IN PUBLIC & PRIVATE SCHOOLS OF LAHORE: TEACHER & PARENT REPORTING - Shahzad, Saadia (Journal of Ayub Medical College Abbottabad, 2021)
Background: The World Health Organization (WHO) estimated that about 10-20% of children worldwide have mental or behavioural problems. Objectives of the study were 1) To determine the prevalence of behavioural problems among primary school children of grade-5 in public and private schools of Lahore upon teachers and parents' reporting 2) To identify association of socio-demographic factors to Total behavioural problems in the study subjects. Methods: descriptive cross-sectional study, conducted in 18 public and private primary schools in Lahore, during 2018-19; with a sample of 396, and simple random sampling technique applied. Inclusion criteria: 1) willingness of the teacher 2) class teacher/ subject teacher 3) teacher has spent >6 months with the class 4) willingness of the parents for their child selection. Exclusion criteria: 1) teachers who had taken part in similar research in the past year 2) child with positive family history of the behavioural problem in siblings 3) child himself/ herself diagnosed for such problem. Data were collected on a standardized Strength and Difficulty Questionnaire. Results: data of 369 students collected through dual informants' survey and analysed. Upon parent reporting the prevalence of total abnormal behavioural problems was 44%; and with teacher reporting 52.85%. Highly significant association was found between gender and type of school (p-value <.001) and teacher outcome. The overall percent agreement for dual informants was 60%. Multiple regression analysis identifies male gender and public-school type to be the predictors of abnormal behaviour problems in primary school children. Conclusion: there is a marked increase in the extent and magnitude of total behaviour problems among male students and in public schools; identified as two significant predictors of the problem.